Horse behaviour : interpreting body language and communication - Schöning, Barbara (Horse riding and management series., 2016)
Authored by an experienced ethologist, this book draws on recent research in the field of equine ethology and applies it to practical knowledge that can be used to improve the relationship between horse and owner. The focus is on interpreting horse body language and signals to enhance understanding and the bond between human and horse.--